THE EFFECT OF USING TABOO GAME TO NINTH GRADERS’ SPEAKING SKILL - Yusup Kuncoro Bowo Susilo (Jurnal Dinamika Pendidikan, 2014)
This study was conducted to improve the ninth graders’ speaking skill. To attain the objective, an experiment was conducted at SMP Pangudi Luhur Jakarta. Thirty five students in the control group were taught speaking in the conventional way, while the thirty nine students in the experimental group were taught by using taboo game. The data collected using tests in both groups were analyzed by using SPSS 15.0 program. The results revealed that there was a significant effect of the implementation the taboo game to the ninth year students’ speaking skill. It was indicated by the result of the statistical calculation that the tcount (=19.395) > ttable (=1.992) with sig. level (=0.05) and d.f (=76). Through the calculation the Ho was rejected and Ha was accepted. Based on the findings, it was concluded that taboo game was significantly effective to improve students’ speaking skill.Keywords : taboo game, speaking skill